Head and Neck Merkel Cell Carcinoma: A 12-Year Single Institutional Experience. (September 2022) - Hurley, C.M.; ALNafisee, D.; Jones, D.; Kelly, J.L.; Regan, P.J.; Hussey, A.J.; McInerney, N.
Abstract: Background: Merkel cell carcinoma (MCC) is an aggressive malignancy of presumed neuroendocrine origin. Most case series of MCC are limited by low case numbers and are not specific to head and neck tumours. The purpose of this study was to provide a focused review of head and neck MCC diagnosis and management in a single Irish institution. Methods: Patient's demographics, tumour characteristics, pathological diagnosis, surgical treatment, adjuvant treatment, subsequent management and clinical course were collected. Estimates of progression-free MCC survival rates were calculated by the Kaplan–Meier statistical model. A Pearson product-moment correlation coefficient examined the association between surgical margins and disease-free follow-up. Results: In total, 11 patients were treated for head and neck MCC with a mean age of 79.6 years (range = 69–91 years). The mean average follow-up duration of patients was 18.3 months. Of the cohort, 18% ( n =2) had a sentinel node biopsy (SLNB). A selective neck dissection was subsequently performed in 18% ( n =2). In total, 72% ( n =8) of patients received adjuvant radiotherapy. Median disease-specific survival was 15 months for the SLNB group and 17 months for the non-SLNB group, not statistically significant ( p =0.23). There was no significant association between surgical margins and disease-free follow ( p =0.65). Conclusions: Our case series adds to a limited body of evidence of head and neck MCC. Surgery remains the treatment priority in localized disease, with an increasing role of SLNB for accurate prognostication and staging. Early management of stage I disease results in moderate long-term disease-free survivability.